ASSOCIATION OF SERUM RENALASE WITH THE RISK OF HYPERTENSION IN CHINESE ADULTS WITH NORMAL KIDNEY FUNCTION. (June 2022) - Wang, Keke; Chu, Chao; Wang, Yang; Yu, Yan; Liao, Yueyuan; Ma, Qiong; Wang, Dan; Zheng, Wenling; Hu, Jiawen; Mu, Jianjun
Abstract : Objective: Renalase, a novel flavoprotein with oxidoreductase activity secreted from kidney and heart into the circulation, plays a crucial role regulating blood pressure. However, research on the relationship between serum renalase and hypertension is controversial. This cross-sectional study is to evaluate the relationship of serum renalase and the risk of hypertension in Chinese adults with normal kidney function. Design and method: We conducted follow-up of the long-term hypertension study cohort established in Hanzhong, Shaanxi Province from April to July 2017. Blood and urine samples were collected and blood pressure was measured. Serum renalase levels were determined using a commercial enzyme-linked immunosorbent assay (ELISA) kit. Data from 2263 subjects was included and nalysed. Results: Serum renalase levels were higher in hypertensive subjects than in normal BP subjects with normal kidney function (2.09 ± 0.55 g/ml vs. 2.17 ± 0.52 g/ml, P < 0.01). Simple correlation analysis revealed that renalase was positively associated with SBP (r = 0.10, P < 0.01) and DBP (r = 0.11, P < 0.11). However, after adjusting confounding factors, logistic regression analysis suggested there was no significant relationship between serum renalase and the risk of hypertension. Further investigation revealed that renalase had a significant interaction effect on hypertension for gender (P for interaction < 0.001), BMI (P for interaction < 0.001) and smoking (P for interaction < 0.001). Those with a BMI above 25 and a renalase above 2.48 g/ml had a higher risk of hypertension. In male and current smokers, subjects with 1.76–2.09 g/ml renalase were more prone to develop hypertension. Conclusions: Our findings suggest that the renalase level in specific populations has heterogeneous effects on blood pressure. Further clinical trials are needed to assess the potential role of renalase as a biomarker of hypertension.